Vulnerability and decision: tension in the medical pact - Von Zuben, Newton Aquiles (O Mundo da Saúde, 2006)
The principle of vulnerability evokes two essential categories of the human being condition: finitude and transcendence. Essentially correlated with the autonomy, dignity and integrity principles, it is the conceptual ground for the reflection on ethical questions stemming from the tension in the doctor-patient relationship. It is in the articulation of these categories that is grounded the process of deliberation and decision process related to therapeutic practices with the patient asking for care and the doctor using the procedures for treatment. It is thus established a pact of trust and an alliance between two moral partners: the patient and the doctor. The vulnerability principle erects as its biggest attribute the respect for the human being, materialized in that situation by the manifes- tation of the patient autonomy by means of the free consent this latter gives after all the clarifications made by the doctor. The conjoining of these principles has constituted even among “moral foreigners” in a “polytheist [and secular] culture” culture (Engelhardt) the shared reference ground, the “ethical intention” and the normative context for decisions in bioethical practice, and one holds as certain the conviction that no universal reason can decide the dilemmas. The aim of this communication is to analyze the heuristic power of the vulnerability principle as a basic concept for human being existence, for it not only reiterates the relevance of respect to the human person but also conditions the opening to the other (responsibility and transcendence) in the ethical intention solicitude and human care as the main “telos” of the medical practice.